Exploring Students’ Needs for Deep Learning-Oriented Islamic Education Materials in Elementary Schools - Hamidah; Abd Muhith; Mashudi (ATTA`DIB, 2025)
Abstract This study explores students’ needs for deep learning-oriented Islamic Education materials at SD Negeri 7 Kediri Tabanan. A qualitative case study approach was employed, using classroom observations, in-depth interviews, and document analysis. The results reveal that current materials remain textual and focus on memorization without contextual application. Teachers face challenges in linking Islamic values to real-life contexts, while students expect more interactive, visual, and applicable learning resources. The findings highlight the urgency of developing Islamic Education materials that promote critical, reflective, and contextual thinking. This study contributes to pedagogical innovation by emphasizing the importance of student-centered material design to enhance meaningful understanding and practice of Islamic values. Keywords: students’ needs, deep learning, learning materials, Islamic Education, elementary school. Abstrak Penelitian ini bertujuan untuk mengeksplorasi kebutuhan siswa terhadap bahan ajar Pendidikan Agama Islam (PAI) yang berorientasi pada deep learning di SD Negeri 7 Kediri Tabanan. Pendekatan penelitian menggunakan studi kasus kualitatif dengan teknik pengumpulan data melalui observasi kelas, wawancara mendalam, dan analisis dokumen. Hasil penelitian menunjukkan bahwa bahan ajar yang digunakan saat ini masih bersifat tekstual dan berfokus pada hafalan tanpa keterkaitan dengan kehidupan sehari-hari. Guru mengalami kesulitan mengaitkan nilai-nilai Islam dengan konteks nyata, sementara siswa membutuhkan bahan ajar yang lebih interaktif, visual, dan aplikatif. Temuan ini menegaskan pentingnya pengembangan bahan ajar PAI yang mendukung berpikir kritis, reflektif, dan kontekstual. Studi ini berkontribusi pada inovasi pedagogis dengan menekankan perlunya desain bahan ajar berbasis kebutuhan siswa untuk memperkuat pemahaman dan pengamalan nilai-nilai Islam secara bermakna. Kata kunci: kebutuhan siswa, deep learning, bahan ajar, Pendidikan Agama Islam, sekolah dasar